RAPID NEURONET INVERSION OF 2D MAGNETOTELLURIC DATA FOR MONITORING OF GEOELECTRICAL SECTION PARAMETERS - Shimelevich M.I.; Obornev E.A.; Gavryushov S. (My University, 2007)
The inverse MagnetoTelluric (MT) operator is approximated by means of the Neural Network (NN). The methodology of the NN interpretation in classes of the geoelectrical sections described by the hundreds of parameters is proposed. Error of the NN inversion and field misfit are evaluated. A rapid NN algorithm solving the inverse problem and detecting changes of time-dependent dynamic parameters of the section is applied to 2D synthetic data.
Keywords: EM MONITORING; MAGNETOTELLURIC INVERSE PROBLEM; NEURAL NETWORK